Analysis of the crashworthiness design and collision dynamics of a subway train. (November 2020) - Xie, Suchao; Du, Xuanjin; Zhou, Hui; Wang, Da; Feng, Zhejun
In this study, the crashworthiness of a subway train was assessed by establishing a finite element model for the first three carriages of the train and the track using the Hypermesh software. By utilising the *MAT_HONEYCOMB material model, a honeycomb in an anti-climbing energy-absorbing device was simulated. Moreover, the process of a subway train – travelling at a speed of 25 km/h – colliding with another identical train in a stationary and non-braking state was simulated by employing the finite element analysis software Hypermesh and LS-DYNA. The process of simulation analysis was divided into two parts: (1) analysis of the anti-climbing energy-absorbing devices under static compression for the investigation of energy absorption and (2) collision analysis of the whole train. The contributions of the proposed energy-absorbing structure – at the end of driver's cab, the coupler and draft gears on each section – to the overall energy absorption in a train collision were calculated. Furthermore, based on the EN15227 standard, the crashworthiness of the train with respect to the survival space for occupants, train acceleration and uplift of wheels relative to the track was evaluated. The coupler of the first carriage fails in a collision at 25 km/h, and the coupler and draft gear are the main energy-absorbing devices. *MAT_HONEYCOMB was used to define the honeycomb materials in anti-climbing energy-absorbing devices and could simulate the mechanical performance thereof. The crashworthiness of the train meets the relevant standard requirements.